Management of Rupture of Prepubic Tendon in a Non-descript Doe Complicated by Evisceration of Gravid Uterus - Sakthivelu, Manokaran; Annadurai, Thangamani; Abdul Rahim, Reshma; Thulasiraman, Sarath; Rama samy, Rajkumar; Ayyasamy, Elango (The Indian Journal of Animal Reproduction, 2026)
A three-year-old goat was presented with the history of swelling in the right-side ventral abdomen and foul-smelling serous discharge from the swollen area. On examination, swollen part had two fistulas. Through one fistula, mild fowl smelling discharge was observed and through another fistula, protrusion of gravid uterine horn was found. On vaginal examination cervix was found to be closed. Based on the clinical findings, the case was diagnosed as longstanding case of hysterocele complicated with evisceration of gravid uterus. On exploratory laparotomy, it was found that the abdominal muscles were not torn and the gravid uterus was eviscerated through the ruptured prepubic tendon. The hysterectomy was performed to save the life of the dam and the doe recovered uneventfully on proper postoperative care.
Keywords: Goat; Hysterocele; Evisceration of uterus; Hysterectomy; Prepubic tendon